LOOKING INTO THE PROCESS OF TEACHING AND LEARNING ENGLISH FOR SPECIFIC PURPOSES (ESP) AT THE UNIVERSITY LEVEL IN INDONESIA: PROBLEMS AND SOLUTIONS - Marisa Yoestara (UNIVERSITAS SERAMBI MEKKAH, 2017)
A number of problems found in the process of teaching and learning English for Specific Purposes (ESP) at universities in Indonesia include the challenges from the students’ side, the lecturers’ side and the university education system’s side. In order to solve the problems, the lecturers are suggested to apply a step-by-step process in the planning stage, started from conducting needs analysis, organizing the course design, and selecting and developing materials. As this solution has been supported theoretically and practically, it is hoped that the process of teaching and learning ESP at the university level in Indonesia will improve, particularly to help students to achieve the specific language learning targets based on their areas of professional.